Influence of drying temperatures on color variation, phenolic compounds, and multi-elemental composition of some culinary-medicinal mushrooms - Nasarudin, Nur-Amirah Izzah; Azilah, Abdul-Malek; Yazid, Nurulain Syuhada Mohamad; Sukor, Rashidah; Raman, Jegadeesh; Raseetha, Siva (Begell House, 2024)
Although mushrooms are widely used for nutraceutical purposes, post-harvest storage is extremely crucial to avoid degradation and quality reduction in fresh mushrooms. Drying treatments are commonly applied in the mushroom industry to extend shelf life. Drying may cause instability of food quality and antioxidant parameters due to unsuitable drying temperatures. Therefore, in this research a common set of temperatures typically used by mushroom growers was applied (50°C, 60°C, 70°C) to Ganoderma lucidum, Lignosus rhinocerus, Auricularia auricula-judae, and Schizophyllum commune to analyze color changes and concentration of elements and phenolic compounds. Mushrooms were chosen based on commonly cultivated species among growers. L. rhinocerus dried at 70°C indicated significantly lower L* (78.90) compared to control (89.94). Element retention in each sample differed depending on the species. The amount of calcium was significantly higher in L. rhinocerus (11,893 mg/kg) and A. auricula-judae (10,941.81 mg/kg) when dried at 60°C. Drying at 70°C resulted in significantly higher magnesium for Sch. commune (13,054.38 mg/kg) and A. auricula-judae (80,56.92 mg/kg). Higher levels of iron and manganese were observed in Sch. commune dried at 70°C (216.54 and 10.02 mg/kg, respectively). Gallic acid had significantly higher retention at 50°C for A. auricula-judae and G. lucidum. Meanwhile, L. rhinocerus and Sch. commune showed significantly higher gallic acid at 60°C. It is evident from these results that temperature does affect the food quality and elemental parameters during the drying process for each mushroom.